Ground Penetrating Radar: Techniques, Applications and Future Prospects – A Comprehensive Review - Soumit Barate; Apurva Naik; Sampurna De; A. A. Bazil Raj (Journal of VLSI Design and Signal Processing, 2025)
This paper provides a detailed overview of Ground Penetrating Radar (GPR) technology, focusing on its basic principles, system designs, and wide range of applications. It explains the core ideas behind GPR operation and the different types of waveforms used, including pulsed, stepped-frequency, and continuous waveforms. GPR systems are grouped based on the technology they use, the frequencies they operate on, and their specific uses, with a look at how well they work for different types of geophysical studies. The paper also classifies GPR antennas, such as dipole, bowtie, and horn antennas and discusses how they affect system performance.